Use of SPECT/CT to Confirm Inconclusive Gastric Emptying Scintigraphy Results. (June 2015) - Henrichon, Stephen; Seltzer, Marc; Siegel, Alan
<x xml:space="preserve">Abstract</x> Abstract A 70-year-old man with cramping, abdominal pain, and diarrhea for 5 months after revision of a Nissen fundoplication underwent further evaluation with solid gastric emptying scintigraphy. On sequential planar images, we were uncertain if activity was present within the stomach or within loops of small bowel. SPECT/CT performed at 4 hours was used to localize the tracer, confirming its presence within the stomach.